The Anatomy of Charisma: Reflections on Political Language and Leadership in Light of Nataliya Petlyuchenko’s Study - Woźniak-Wrzesińska, Ewelina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
Review of the Monograph The Linguistics of Charisma by Nataliya Petlyuchenko